SELF-DEVELOPMENT OF ORGANIZATIONAL ABILITIES OF STUDENTS IN EXTRACURRICULAR ACTIVITIES OF THE HIGHER EDUCATIONAL INSTITUTION OF THE SYSTEM OF THE MINISTRY OF INTERNAL AFFAIRS OF UKRAINE (Pedagogy of Higher and Secondary Education, 2022)
Positive influence of technology of forming of organizational capabilities is certain on their self-development in the out of class activities of higher scientific establishment of Ministry of Internal Affairs of Ukraine.
Keywords: self-development; organizational capabities; students; extracurricular activities